Impact of perioperative chemotherapy on postoperative morbidity after gastrectomy for gastric cancer - Cabral, Francisco (2021)
Introduction: The use of perioperative chemotherapy (CT) in patients with advanced gastric carcinoma increases their overall survival. This therapy may also increase the number of patients with R0 resection. Potential drawbacks of this therapy, besides its toxicity, include increased surgical morbidity. Methods: We retrospectively evaluated the records of patients undergoing gastrectomy with curative intent, for carcinoma, at our institution between January 2009 and August 2018. They were divided into two groups: direct surgery (SURG) and perioperative CT (CHEMO). Patients with other neoadjuvant therapies and cardia Siewert I and II carcinomas were excluded. The primary objective was to evaluate the impact of perioperative CT on surgical morbidity. As secondary objectives, resection radicality and total lymph node count were compared between the two groups. Results: A total of 307 patients (97 direct surgery and 210 perioperative CT) were evaluated. Median age was 67 years old. The overall major surgical morbidity (Clavien-Dindo 3-5) was 10.6% in the CHEMO group and 12.4 in the SURG group (p = 0.643). There was no statistically significant difference between the surgical radicality (R0 98% in the SURG group vs 97.5% CHEMO group (p = 0.865). There was an increase in the total number of lymph nodes retrieved in the specimen in the CHEMO group (25 vs 22, p = 0.001), a difference that was not maintained in the subgroup analysis as a function of the surgery performed. Conclusions: Perioperative CT in gastric carcinoma does not increase surgical morbidity, surgical radicality and total lymph node count. (C) 2020 AEC. Published by Elsevier Espana, S.L.U. All rights reserved.